Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar Sosiologi Siswa - Fawziah Zahrawati (Indonesian Publication Center, 2020)
This study aims to improve the sociology learning outcomes of class X Madrasah Aliyah Muhammadiyah Salaka students, Takalar Regency through the application of the Problem Based Learning model. This type of research is a Class Action Research consisting of two cycles with 4 stages, namely: planning, action, observation and reflection which is done repeatedly. This research was conducted at Madrasah Aliyah Muhammadiyah Salaka, Takalar Regency. The subjects of the study were class X students with 21 students, consisting of 10 male students and 11 female students. The results showed that an increase in student sociology learning outcomes in the first cycle the average value from 71.43 to 77.86 in the second cycle. In addition, this learning model can increase student attendance, student attention, student activity, and reduce students who carry out negative activities during the learning process.